Analisis Kebutuhan Penilaian Psikomotor Berdasarkan Video Tutorial Berlandaskan Manualbook pada Pendidikan Vokasi Guna Meningkatkan Pencapaian Learning Target - Rifdarmon Rifdarmon (Universitas Negeri Padang, 2020)
The purpose of this study is to look at the needs and potential of the Department of Automotive Engineering for the video tutorial assessment model as an evaluation of learning and achievement of student learning targets in LEO course practice. Vocational education in Indonesia is one example or concrete evidence that the Indonesian government is serious about building a smart generation to realize the ideals of the nation. Educating the life of the nation means continuing to develop the quality of education so that Indonesia is not left behind by other nations, especially in the field of education. Vocational education in Indonesia requires professional educators who are able to direct learners towards predetermined learning goals. A professional educator certainly understands that the learning process consists of three main stages namely, preparation, implementation and evaluation. Student competency evaluation consists of 3 components that must be evaluated, cognitive competency evaluation, affective competency evaluation, and psychomotor competency evaluation. The research will be conducted using descriptive research methods, where this research will describe the need for video tutorials as one of the models to measure the psychomotor abilities of students in LEO courses. From the descriptive research that has been conducted on the needs analysis of Psychomotor Assessment Based on Video Tutorials Based on Manualbooks on Vocational Education to Improve Learning Targets Achievement, it can be seen that LEO students in making video tutorials as a material for evaluating psychomotor competencies reap good responses from students and lecturers. Based on this research, it can be seen that automotive engineering students at the Padang State University Engineering Faculty are greatly assisted in the process of assessing one's own abilities, and lecturers can also assess student competency as a whole from each topic that has been studied or comprehensively.